DOCTOR ĐORĐE JOANOVIĆ, THE FATHER OF SERBIAN ONCOLOGY - PILJIĆ, DIJANA (Medicinski časopis, 2025)
Đorđe Joanović was born in Vienna on June 16, 1871, to mother Marija Joanović, born Vlahović, and father Harinton Joanović. The Joanović family originates from the village of Beodre. He left his Viennese university career, scientific works and famous Viennese laboratories and came to Belgrade after the end of the First World War with a great desire as a patriot to help Serbia. Doctor Đorđe Joanović was an innovative scientist, a pioneer in the field of laboratory study of oncological diseases and the epidemiology of carcinogenesis, and in that field he was world-renowned and respected. Doctor Joanović is one of the founders of the Faculty of Medicine in Belgrade. He initiated the establishment of the then most modern Institute of Pathology in Belgrade. Doctor Joanović founded and became the first president of the Yugoslav Society for the Study and Suppression of Cancer. He was elected four times as the dean of the Faculty of Medicine in Belgrade. Professor Đorđe Joanović was a respected member of Matica Srpska in Novi Sad and a senior scientific associate of the Serbian Academy of Sciences. He was elected an honorary member of the German and Czech Oncological Committee for the Suppression of cancer. He was the permanent representative of the Kingdom of Yugoslavia in Paris at the International Office for Public Hygiene. He was elected president of the Yugoslav and Serbian Medical Association, as well as the representative of the Kingdom of Yugoslavia in the All-Slovenian Medical Association. Doctor Đorđe was also a member of the Medical Council of the Army of the Kingdom of Yugoslavia, as well as a professor of Military Health. Professor Joanović was a member of the Committee of the International Institute for Geographical Pathology. He became the founder and president of the Fund for Helping Poor Students.He was also the editor of the Serbian Archive for All Medicine, as well as a member and correspondent of numerous editorial offices of medical journals. The Institute of Pathology in Belgrade, the Elementary School in Novi Milosevo and the General Hospital in Zrenjanin bear the name "Doctor Đorđe Joanović".Keywords: doctor Đorđe Joanović, Institute of Pathology Belgrade, oncology, epidemiology of carcinogenesis.
Keywords: doctor Đorđe Joanović; oncology; Institute of oncology; etiopatogenesis carcinoma